Phase angle and water cell distribution as inflammation indicators linked to hematological markers across BMI categories - Farzam Kamrani; Maryam Mohammadzadeh; Seyyed Reza Sobhani; Zahra Khorasanchi (Scientific Reports)
Abstract The Phase Angle (PhA) and water cell distribution ratios are essential indicators of inflammation linked to serum inflammatory markers. We aim to investigate the relationship between PhA and extracellular water to total body water (ECW/TBW) ratio with hematological inflammatory markers. The study utilized data from the PERSIAN Organizational Cohort Study in Mashhad (POCM), incorporating information from bioelectrical impedance analysis (BIA) and blood tests. It examined two groups: individuals of normal weight (N = 1654) and those categorized as overweight or obese (N = 3651). In addition to Hemoglobin (Hgb), hematocrit (Hct), Platelet (Plt), White blood cell (WBC) and its components, the study also computed various hematologic inflammatory markers, such as platelet to HDL ratio (PHR), platelet to lymphocyte ratio (PLR), monocyte to HDL ratio (MHR), lymphocyte to HDL ratio (LHR), RDW to lymphocyte ratio (RLR), RDW to platelet ratio (RPR), and granulocyte to lymphocyte ratio (GLR). In the adjusted model, an increase in PhA is linked to increases in Hgb (Normal-weight: 17.1%, BMI > 25: 12.3%) and Hct (Normal-weight: 15.3%, BMI > 25: 13.6%), WBC (Normal-weight: 9%, BMI > 25: 6.8%), and RPR (Normal-weight: 17.1%, BMI > 25: 12.3%). Additionally, in the BMI > 25 categories, an increase in PhA is associated with increases in Plt (16.7%), Lymphocytes (5.6%), and PHR (5.2%). Furthermore, there is a decrease in RPR (Normal-weight: 7.4%, BMI > 25: 6.6%) with a unit increase in PhA. A unit increase in ECW/TBW is associated with a decrease in Hgb (Normal-weight: 19.9%, BMI > 25: 17.3%) and Hct (Normal-weight: 17.8%, BMI > 25: 17.6%). This is also linked to decreased WBC (9.6%) in the normal-weight category. Furthermore, in the BMI > 25 category, there are decreases in Plt (5.5%), RLR (6.5%), RPR (6.9%), GLR (5.9%), Granulocytes (7.5%), and Lymphocytes (8.3%) with an increase in ECW/TBW. The findings revealed that ECW/TBW demonstrates a stronger correlation with hematological markers than PhA, with these associations being particularly significant among normal-weight individuals. These results highlight the need for further research to explore the underlying mechanisms driving these relationships.